Pela tela, pela janela : as funcionalidades da tela interativa em aplicativos de arte para dispositivos móveis (ipads) - Ribeiro, Gabriela Silva (2015)
This paper presents an investigation about the role played by mobile devices as mediators of a new social reality in which behaviors, relations and events are guided by a hybrid logic that works between the virtual and physical (non-virtual). We start by